(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Calprotectin is a heterodimeric compound belonging to the S100 family, it is mostly produced in leukocytes and is implicated in various human disorders, including tumors and autoimmune diseases. Objective: To evaluate the usefulness of calprotectin serum level as a valid target for monitoring progression of rheumatoid arthritis (RA) disease and response to tumor necrosis factor-alpha (TNF-?) inhibitor therapy (Infliximab). Methods: This case-control study comprised 150 participants, consisting of 50 healthy individuals and 100 patients with RA on anti-TNF-? (Infliximab) therapy (50 responders and 50 non-responders). The concentration of calprotectin in the serum was determined using the enzyme-linked immunosorbent assay. Results: The clinical disease activity index revealed a substantial distinction between patients, specifically responders and non-responders (P